1983
DOI: 10.5465/amr.1983.4287709
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Effectiveness: An Alternative Perspective

Abstract: A paradigm is proposed that views effectiveness as the ability of an organization to account successfully for its outputs and operations lo its various infernal and external constituencies. This framework can he used to assess effectiveness by examining organizational outputs and processes in a critical and holistic way. A review of (he existing literatures on organizational effectiveness and a case example are used to develop the proposed framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 10 publications
0
19
0
2
Order By: Relevance
“…Although organizational effectiveness has been widely studied across disciplines, consensus has not been achieved on a common definition or a common set of effectiveness criteria. Gaertner and Ramnarayan (1983) propose that organizational effectiveness is "not a thing, or a goal, or a characteristic of organizational outputs or behaviors, but rather a state of relationship within and among relevant constituencies of the organization" (p. 97). Another definition includes "the ability of an organization to account successfully for its outputs and operations to its various internal and external constituencies" (Gaertner & Ramnarayan,p.…”
Section: Organiz Ational Performance Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although organizational effectiveness has been widely studied across disciplines, consensus has not been achieved on a common definition or a common set of effectiveness criteria. Gaertner and Ramnarayan (1983) propose that organizational effectiveness is "not a thing, or a goal, or a characteristic of organizational outputs or behaviors, but rather a state of relationship within and among relevant constituencies of the organization" (p. 97). Another definition includes "the ability of an organization to account successfully for its outputs and operations to its various internal and external constituencies" (Gaertner & Ramnarayan,p.…”
Section: Organiz Ational Performance Effectivenessmentioning
confidence: 99%
“…This short form includes five items measured by a five-point scale from 1 (strongly disagree) to 5 (strongly agree). Finally, a short form of the Gaertner and Ramnarayan (1983) model was used to measure organizational performance effectiveness and benefits; this model includes eight items assessed on a five-point scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Measures and Scalesmentioning
confidence: 99%
“…Evaluation often promises "not a particular product, but a particular role, asserting not a thing done, but a capacity or need to be able to do that thing and other things like it" (Gaertner and Ramnarayan, 1983:103). The rules of the game for establishing oneself as a "proper" organization are far from equivalent to the rules of the game by which an organization documents its productivity or satisfies customers, clients, and the like (Gaertner and Ramnarayan, 1983). An evaluation procedure may for instance signal legitimacy towards other organizations, controlling authorities, and so on, over and above whether customers are served and whether steps are taken as a result of the evaluation.…”
Section: Organizational Identitiesmentioning
confidence: 99%
“…Although goal measurement has been a popular approach, studies have shown limitations to this technique, when, for example, other internal and external environmental influences are not considered (Campbell, 1977, Gaertner, 1983Van De Ven & Ferry, 1980;Zammoto, 1982); nor differences in intra-and interorganizational goals (Marsh & Mannari, 1976).…”
mentioning
confidence: 99%
“…Van De Ven & Ferry (1980) presented a detailed assessment procedure at micro-and macro-levels covering dimensions of organizational context, structure, and performance, obtained through subjective employee reports. Gaertner and Ramnarayan (1983) also combined approaches by analyzing reports on the following: (1) how activities are monitored and how they change over time; and (2) how activity reports converge with member perceptions, with their respective activities, and with other reports.…”
mentioning
confidence: 99%